Fundamental study on use of coir fibre boards as a roofing material - Weerasinghe, Hilary Lal Shanti Devapriya; Tanabe, Tadaaki; Cook, David J.; The Government of New Zealand (Bangkok : Asian Institute of Technology, 1977)
This study is aimed at investigating the feasibility of using a composite made of coir fibre and cement as a low-cost roofing material for tropical countries. Varied mix proportions of fibre and cement and different fibre lengths were used in the study with different casting pressures to determine the mechanical properties and evaluate the performance characteristics under service conditions. Bending tests, compression tests, water absorption, permeability, shrinkage, fire resistance tests, impact resistance tests and exposure tests were conducted. The test results indicate that coir fibre boards can be used for roofing in tropical countries.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M. Eng.) - Asian Institute of Technology, 1977
Keywords: Coir; Building materials -- Research